Analyses of the similarity and difference of global gene expression profiles in cortex regions of three neurodegenerative diseases: sporadic Creutzfeldt-Jakob disease (sCJD), fatal familial insomnia (FFI), and Alzheimer's disease (AD) - Tian, Chan; Liu, Di; Xiang, Wei; Kretzschmar, Hans A.; Sun, Qing-Lan; Gao, Chen; Xu, Yin; Wang, Hui; Fan, Xue-Yu; Meng, Ge; Li, Wei; Dong, Xiao-Ping (Molecular Neurobiology, 2014)
Neurodegenerative disease is a general designation for the disorders that are progressive loss of structure or function and final death of neurons, including Alzheimer's, Parkinson's, Huntington's, prion diseases, etc. In this study, we comparatively analyzed 21 individual microarray data sets of the cortex tissues from 11 sporadic Creutzfeldt-Jakob disease (sCJD), 3 fatal familial insomnia (FFI), 3 Alzheimer's disease (AD), and 4 normal controls. After normalization, a collection of 730 differently expressed sets (DESets) were obtained by comparison of the data of three diseases with their original controls. Principal component analysis (PCA) showed a background-related distribution within the groups of FFI, AD, and normal control, but two apparently different subgroups within the group of sCJD were observed. Review of the clinical materials of 11 sCJD patients identified the difference in brain PrP(Sc) deposits between two subgroups. Hierarchical cluster analysis illustrated the relatively independent clusters of normal controls, FFIs, six sCJD cases (subgroup 1) with more PrP(Sc) deposits, respectively, while an overlapped cluster of five cases of sCJD2 (subgroup 2) with less PrP(Sc) deposits and AD patients. Despite of the presence of special gene expressions, many common features were found among those neurodegenerative diseases. The most commonly changed biological processes (BPs) were signal transduction, synaptic transmission, and neuropeptide signaling pathway. The most commonly changed pathways were MAPK signaling pathway, Parkinson's disease, and oxidative phosphorylation. Our data here provide the similarity and difference in global gene expressions among the patients with sCJD, FFI, and AD, which may help to understand the common mechanism of neurodegenerative diseases.
EVALuna2:4697